Activating nuclear xenobiotic receptors and triggering ER stress and hepatic cytochromes P450 systems in quails (Coturnix C. coturnix) during atrazine exposure. Issue 6 (10th February 2017) - Du, Zheng‐Hai; Qin, Lei; Lin, Jia; Sun, Yan‐Chun; Xia, Jun; Zhang, Cong; Li, Xue‐Nan; Li, Jin‐Long
Abstract: Atrazine (ATR) is one of the most widely detected contaminant in the ecosystem. Nuclear xenobiotic receptors are activated by herbicides and induce the transcription of CYP450 isoforms involved in xenobiotic metabolism and transport. However, little is known about hepatic nuclear xenobiotic receptors in birds are responsible for ATR‐induced hepatotoxicity via regulating the cytochrome P450 enzyme systems (CYP450s). The objective of this study was to investigate the mechanism of ATR hepatotoxicity in quails. For this purpose, male quails were dosed by oral gavage from sexual immaturity to maturity with 0, 50, 250, and 500 mg/kg/day ATR for 45 days. The results showed that ATR exposure caused the hepatotoxicity damage and endoplasmic reticulum (ER) degeneration. It suggested that ER is a target organelle of ATR toxicity in hepatocytes. ATR exposure disrupted the hepatic CYP450s homeostasis. This study also demonstrated that ATR triggered the CYP450 isoforms transcription via activating the hepatic CAR/PXR pathway. The present study provides new insights regarding the mechanism of the ATR‐induced hepatotoxicity through activating nuclear xenobiotic receptors and triggering ER stress and hepatic CYP450s in quails.